2016
DOI: 10.1007/s00432-016-2291-4
|View full text |Cite
|
Sign up to set email alerts
|

Resin-based Yttrium-90 microspheres for unresectable and failed first-line chemotherapy intrahepatic cholangiocarcinoma: preliminary results

Abstract: Resin-based Y radioembolization can provide palliative control of unresectable and failed first-line chemotherapy ICC in a salvage setting with acceptable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
5
26
1
Order By: Relevance
“…These results were consistent with previous study, which show that radiotherapy did not provide a survival benefit for resection patients with positive resection margins and node negative ICC [22]. Recent studies also demonstrated the benefits of radiation in unresectable ICC [10], [23], [24].…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with previous study, which show that radiotherapy did not provide a survival benefit for resection patients with positive resection margins and node negative ICC [22]. Recent studies also demonstrated the benefits of radiation in unresectable ICC [10], [23], [24].…”
Section: Discussionsupporting
confidence: 92%
“…In patients with cirrhosis (12 patients), liver toxicity appeared higher than in non-cirrhotic Median progression-free survival was 14 months [95%CI: [8][9][10][11][12][13][14][15][16][17], with a 12-months PFS rate of 55% and 24-months PFS rate of 30% ( Figure 3A). Median OS was 22 months [95% CI: 14-52], with a 12-months OS rate of 75% and 24-months OS rate of 45% ( Figure 3B).…”
Section: Treatment Received and Safetymentioning
confidence: 99%
“…Radiolabeled microspheres are administrated via the hepatic arteries, delivering a local radiation dose when reaching the tumor vasculature. Multiple single-center series reported results of RE in BTC [6][7][8][9][10][11][12][13][14][15][16][17], however the largest published to date included only 46 patients [11]. There is still considerable uncertainty about potential prognostic factors and about the potential preferred population in which this treatment should be applied [15,18].…”
Section: Introductionmentioning
confidence: 99%